2016
DOI: 10.1007/s11999-016-4819-y
|View full text |Cite
|
Sign up to set email alerts
|

Is Assessment of Femoral Head Perfusion During Modified Dunn for Unstable Slipped Capital Femoral Epiphysis an Accurate Indicator of Osteonecrosis?

Abstract: Background The modified Dunn procedure, which is an open subcapital realignment through a surgical dislocation approach, has gained popularity for the treatment of unstable slipped capital femoral epiphysis (SCFE). Intraoperative monitoring of the femoral head perfusion has been recommended as a method of predicting osteonecrosis; however, the accuracy of this assessment has not been well documented. Questions/purposes We asked (1) whether intraoperative assessment of femoral head perfusion would help identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
(54 reference statements)
1
19
0
2
Order By: Relevance
“…To date, none of our patients, including some with 5 years of follow-up and those in our study 3 with a minimum follow-up of 2 years, have developed osteonecrosis. Recent studies have validated the use of the ICP probe in monitoring for epiphyseal perfusion in patients undergoing a modified Dunn procedure for unstable SCFE, finding it an effective technique for identifying patients who may go on to develop osteonecrosis 4,5 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, none of our patients, including some with 5 years of follow-up and those in our study 3 with a minimum follow-up of 2 years, have developed osteonecrosis. Recent studies have validated the use of the ICP probe in monitoring for epiphyseal perfusion in patients undergoing a modified Dunn procedure for unstable SCFE, finding it an effective technique for identifying patients who may go on to develop osteonecrosis 4,5 .…”
Section: Resultsmentioning
confidence: 99%
“…The intraoperative assessment of femoral head perfusion is becoming increasingly common when treating SCFEs [ 31 , 32 ]. Many studies have now published results suggesting that this may be a more accurate and easier way to predict the development of AVN rather than previously described methods such as MRI, bone scan or angiography [ 14 , 19 ]. It also has the benefit of real-time adjustment of ostectomy and reduction position to ensure adequate head perfusion is maintained.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of assessing femoral head perfusion that have been described are evaluation of bleeding by creating a drill hole [ 16 , 29 , 33 ], the use of Laser Doppler Flowmetry [ 17 , 20 ] and intracranial pressure monitoring (ICP) [ 14 , 19 ]. Assessing bleeding via a drill hole is a simple way to assess femoral head perfusion but can only be done with open surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that blood flow was restored after reduction for four of six patients who did not have arterial flow to the femoral head on the preoperative angiogram. Novais et al 37 used different techniques in the perioperative setting for 29 patients with unstable SCFE who underwent a capital realignment procedure to evaluate the restoration of blood flow to the femoral head during the operation. They concluded that assessment of femoral head blood perfusion can be used as a predictor of the later development of AVN.…”
Section: Discussionmentioning
confidence: 99%